Clock component and method for manufacturing clock component

The method addresses inefficiencies in coloring small watch glasses by introducing a colored chemical element and heat-treating the transparent watch components, achieving precise, high-quality coloration while maintaining mechanical properties.

JP7659370B2Active Publication Date: 2025-04-09ROLEX SA
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020022566
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-02-18
Filing Date
2020-02-13
Publication Date
2025-04-09
Estimated Expiration
2040-02-13

AI Technical Summary

Technical Problem

Existing methods for coloring small watch glasses, typically made of sapphire, are inefficient, requiring time-consuming color changes, inability to color specific parts or combine colors, and often result in insufficient quality or unsuitable colors for watch applications.

Method used

A method involving a transparent watch component with a modified chemical composition band introduced by depositing at least one colored chemical element on the surface, followed by heat treatment to achieve a transparent, colored piece with predictable and reproducible results.

Benefits of technology

The method allows for precise control over color introduction and heat treatment, resulting in transparent, colored watch components with maintained mechanical strength and surface hardness, achieving desired color homogeneity and transparency suitable for watch components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659370000007
    Figure 0007659370000007
  • Figure 0007659370000008
    Figure 0007659370000008
  • Figure 0007659370000009
    Figure 0007659370000009
Patent Text Reader

Abstract

To provide a solution for obtaining a transparent and colored timepiece component, which excludes all or some of prior-art drawbacks.SOLUTION: A transparent timepiece component, in particular a small sized watch glass, includes a substantially planar or curved interior surface 1, and contains mainly a transparent material colored by a zone 30 of a modified chemical composition within the component through introduction of at least one coloring chemical element into the transparent material, where the zone of the modified chemical composition extends in only one part of a thickness of the timepiece component.SELECTED DRAWING: Figure 2b
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent tinted timepiece component, in particular a small watch glass. The present invention also relates to a timepiece, such as a wristwatch, comprising such a timepiece component. The present invention further relates to a method for producing a timepiece component, in particular comprising a step of tinting a transparent substrate. [Background technology]

[0002] Small watch glasses made of sapphire are originally transparent and colorless, and it may be necessary to change their appearance in order to color the glass. For this reason, there are methods for synthesizing sapphire and coloring it at the same time. According to this method, sapphire spheres are produced, which are colored in bulk, and then the small watch glasses are cut out. Such a method is disclosed, for example, in US Pat. No. 5,399,363. This conventional solution has a number of drawbacks: -Every color change requires tedious consideration; - It is not possible to color only some parts or combine several colors. -It is not possible to achieve some specific colors that are not available or of sufficient quality, so it may not be suitable for watch applications.

[0003] In addition to the above comments, any manufacturing method for a watch component must consider numerous constraints, and the introduction of a coloring step into the manufacturing method must not decrease the overall quality of the resulting watch component. For example, in the example of a small watch glass, the following watch requirements must be achieved: The glass must be sufficiently transparent to make it possible to read the time. The glass must have high overall mechanical strength and surface scratch resistance. The tinting of such glass must make it possible to obtain predictable and reproducible results. - The colours to be recognised must be free of defects and have the quality of perfect homogeneity or exact blending according to the specified selection. -The color obtained must be suitable for a watch, especially for the dial, which can be seen through the glass.

[0004] These technical problems also apply to other transparent watch components, in particular having a substantially planar shape, in particular having a substantially planar or curved inner surface and / or made of mineral materials such as sapphire or glass. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2017 / 187647 Summary of the Invention [Problem to be solved by the invention]

[0006] The general object of the present invention is to provide a solution for obtaining transparent and colored watch components that does not suffer from all or some of the disadvantages of the prior art.

[0007] More particularly, the object of the invention is to obtain a transparent and colored watch component and a manufacturing method that makes it possible to achieve a reproducible and accurate appearance of excellent quality. [Means for solving the problem]

[0008] To this end, the invention is based on a transparent timepiece component, in particular a small watch glass, with a substantially planar or curved inner surface, which mainly comprises a transparent material coloured by a zone of chemical composition modified in said component by introducing at least one colouring chemical element into said transparent material, said zone of modified chemical composition extending over only a portion of the layer thickness of said timepiece component. Advantageously, this zone of modified chemical composition does not extend over the entire volume of the timepiece component. More advantageously, this zone does not extend over the entire thickness of the timepiece component. More advantageously, this zone extends only over a small portion of the thickness and / or volume of the timepiece component.

[0009] The present invention further comprises: a. providing an initial substrate including a substantially planar or curved inner surface comprised primarily of a transparent material; b. introducing at least one coloring chemical element through at least one outer or inner surface of said initial substrate; c. heat treating the substrate resulting from the incorporation step containing at least one coloring chemical element to obtain a transparent colored piece. The present invention relates to a method for producing a colored transparent watch component, comprising the steps of:

[0010] Advantageously, the introducing step comprises depositing a coating which includes at least one colouring chemical element.

[0011] The invention is defined in more detail by the claims.

[0012] The above objects, features and advantages of the present invention will be explained in more detail in the description of specific embodiments given below as non-limiting examples in conjunction with the accompanying drawings. [Brief description of the drawings]

[0013] [Figure 1a] 1a-c show cross-sectional views of the thickness of a substrate in the previous form of a watch component according to several variants of an embodiment of the invention. [Figure 1b]1b respectively show cross-sectional views through the thickness of a substrate in the previous form of a watch component according to several variants of an embodiment of the invention. [Figure 1c] 1c respectively show cross-sectional views of the thickness of a substrate in the previous form of a watch component according to some variants of an embodiment of the invention. [Figure 1d] FIG. 1d shows cross-sectional views of the thickness of a substrate in the previous form of a watch component according to several variants of an embodiment of the invention. [Figure 1e] FIG. 1e shows cross-sectional views of the thickness of a substrate in the previous form of a watch component according to several variants of an embodiment of the invention. [Figure 2a] Figure 2a shows a cross-sectional view of the thickness of a substrate in the previous form of a watch component after carrying out a first manufacturing step and then a second manufacturing step, respectively, of a manufacturing method according to an embodiment of the present invention. [Figure 2b] Figure 2b shows a cross-sectional view of the thickness of a substrate in its previous form of a watch component after carrying out a first manufacturing step and then a second manufacturing step, respectively, of a manufacturing method according to an embodiment of the present invention. [Figure 3a] FIG. 3a shows a comparison of the transmittance (T) as a function of wavelength (L) of different glasses made of sapphire according to a first example, obtained by different variants of the manufacturing method according to an embodiment of the present invention. [Figure 3b] FIG. 3b is an enlarged view of FIG. 3a. [Figure 3c] Figure 3c shows an image obtained using a transmission electron microscope (TEM) of a thin section taken from a stained transparent piece resulting from carrying out a manufacturing method according to an embodiment of the invention, with the inset showing an electron diffraction image obtained in a zone close to the surface (at a distance d or less from the surface). [Figure 4] FIG. 4 shows the transmittance (T) as a function of wavelength (L) of various sapphire glasses according to example 2 obtained by several different variants of the manufacturing method according to an embodiment of the invention. [Diagram 5]FIG. 5 shows the transmittance (T) as a function of wavelength (L) of various sapphire glasses according to Example 3 obtained by several different variants of the manufacturing method according to an embodiment of the present invention. [Figure 6] 6a to 6c show the transmittance (T) as a function of wavelength (L) of various sapphire glasses according to example 4 obtained by several different variants of the manufacturing method according to an embodiment of the present invention. [Figure 7] FIG. 7 shows the transmittance (T) as a function of wavelength (L) of various sapphire glasses according to example 5 obtained by several different variants of the manufacturing method according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] For ease of description, the same reference numbers are used for identical or equivalent features in the various variants.

[0015] Furthermore, for ease of explanation below, the adjective "external" refers to the volume or surface of a watch component that is intended to face towards the outside of the watch, including in particular the volume or surface that is directly visible to an observer looking at the watch. Conversely, the adjective "internal" refers to the volume or surface of a watch component that is intended to face towards the inside of the watch. Although not precise, the adjectives "external" and "internal" refer to a volume or surface that is entirely located inside the watch, whose outer surface is closest to the outer boundary of the watch.

[0016] Furthermore, the adjective "transparent" is used to refer to the property of a material if it provides a transmission, evaluated by a transmittance Y, of 68% or more, or 79% or more, of radiation that at least includes wavelengths in the visible range. The term "transparent material" is understood to mean a material that, in combination with its nature and the thickness used, is at least partially transparent to said radiation. Advantageously, the transparent material used is also at least partially transparent to radiation that includes wavelengths in the ultraviolet range.

[0017] An embodiment of the invention is described below as a method for manufacturing a sapphire crystal for a watch. The same method can also be employed for other watch components, as will be described later. This manufacturing method comprises, following the previous step E0 of providing a transparent substrate, i.e. a substrate mainly comprising a transparent material, two main steps constituting a colouring stage or colouring method: - E1, the introduction of a coloring chemical element into at least one of the outer or inner surfaces of the substrate, also called the initial substrate; E2 heat treating the substrate resulting from the incorporation step, comprising at least one colouring chemical element, in order to obtain transparent and coloured pieces.

[0018] As mentioned above, the manufacturing method carries out a previous step E0 of providing an initial substrate 10. This substrate advantageously has a substantially planar shape, including an outer surface intended to face towards the outside of the watch and an inner surface, substantially planar or curved, intended to face towards the inside of the watch. This substrate advantageously consists entirely of a transparent material. This transparent material may be colourless. As a variant, this material may be coloured. However, the method can also be applied to transparent pieces of a substrate that are only locally transparent.

[0019] In an embodiment, the transparent material is sapphire, in particular monocrystalline synthetic alumina. Alternatively, the material may be an at least partially inorganic and / or mineral transparent material, such as, for example, glass (borosilicate glass, photostructurable glass, etc.), corundum, alumina, yttrium aluminum garnet (YAG), glass ceramics and / or monocrystalline or polycrystalline ceramics. The transparent material may also be a pre-colored transparent material as mentioned above, such as colored alumina.

[0020] The initial substrate may furthermore advantageously have the same or a similar shape as the future glass, which may be modified by subsequent steps, for example machining. The substrate may further advantageously have the same surface finish as the future glass. The outer and / or inner surfaces are preferably finished. Alternatively, it may have another surface finish, especially locally.

[0021] The outer and / or inner surface may be planar. Alternatively, it may be curved, for example concave or convex. The outer and / or inner surface is preferably continuously curved, in other words it does not consist of juxtaposed facets. However, the outer and / or inner surface may include bevels or chamfers, in particular at the peripheral height, as described below.

[0022] Alternatively, at least one of the inner or outer surfaces may include features, in particular indicating time indications or indications derived from time, for example by creating, by machining, raised and / or recessed structural bands.

[0023] 1a to 1e show examples of substrates, called initial substrates, proposed for a previous step for producing a small watch glass, according to several implemented variants.

[0024] FIG. 1a thus constitutes an initial substrate 10 according to variant 1, which comprises a planar outer surface 2 forming a surface P2, parallel to a planar inner surface 1 forming a surface P1. The substrate further comprises, at its periphery, a side surface 3 forming a planar cylindrical third surface extending perpendicularly from the outer surface 2 to the inner surface 1 of the substrate, over the entire periphery of the substrate. The total thickness e of the initial substrate is defined as the distance between the outer surface 2 and the inner surface 1. In particular, the total thickness e is measured perpendicularly to the surface P1, in particular to the inner surface 1 in a direction p perpendicular to the surfaces P1 and in particular to the surfaces P1 and P2. The substrate may have any shape, advantageously a shape corresponding to the watch to be mounted in the future, for example circular, elliptical, rectangular, etc. Advantageously, for the purpose of producing monoculars and magnifying lenses, the substrate is formed from a material having a thickness of 20 mm. 2 or for the purpose of manufacturing small watch glasses, 2 or more, or 200mm 2 or more, or 300mm 2 The inner surface has an area of ​​at least one of the above.

[0025] FIG. 1b shows an initial substrate 10 according to a second variant, which differs from the variant substrates in that the side surface 3 includes a portion 4 forming a bevel formed on the periphery of the outer surface 2. This beveled portion 4 is cut and extends between the outer surface 2 and the remaining side surface 3 (between the plane P2 and the intermediate plane P3 parallel to the plane P2). The remainder of the side surface 3 remains perpendicular to the inner surface 1. Advantageously, this beveled portion extends over the entire periphery of the substrate. The beveled portion 4 extends over a thickness f of the substrate measured perpendicularly to the planes P2 and P3, which is slightly less than half the total thickness e of the substrate. Preferably, the thickness f is between 0.07 and 0.6 times the total thickness e of the substrate. The beveled portion 4 makes a constant angle α with the direction p. Advantageously, the angle α is between 30° and 80°. Alternatively, the angle α and / or the thickness f may vary around the periphery of the glass.

[0026] FIG. 1c shows the initial substrate 10 according to variant 3, which constitutes an intermediate solution between the two variants described above. The at least partially planar side surface 3 is replaced by a curved side surface 3, which connects the two outer and inner surfaces by a continuous curve. The curved surface forming the side surface 3 can be characterized at each point by an angle α, defined as the angle between the tangent of the curved surface and the direction p. This angle α is variable, but remains greater than or equal to 30° in a first part of the side surface 3 on the side of the outer surface 2. The remaining curved surface forming the side surface 3 on the side of the inner surface 1 can be perpendicular or substantially perpendicular to the inner surface 1, with the angle α being equal to or inclined towards 0°. This first part of the side surface 3 resembles the inclined surface 4 in variant 2.

[0027] FIG. 1d shows an initial substrate 10 according to variant 4, in which the two faces, the outer face 2 and the inner face 1, are curved in the same and parallel shape. The outer wall is arranged symmetrically around the central axis, the apex is defined as the outermost point of the outer face 2, and the face P2 is defined as the face tangent to this curved outer face 2 and passing through this apex. This face P2 thus corresponds to the outermost face of the outer face 2. Similarly, the innermost points of the inner face 1, i.e. the points defining the periphery of the inner face, define a face P1 tangent to the inner face 1 and parallel to the face P2. The direction p is defined as the direction perpendicular to the face P1, in particular to the faces P1 and P2. The total thickness e of the substrate is again defined as the distance between the two faces P1 and P2, the total thickness e being measured perpendicular to the face P1 along the direction p. The side face 3 constitutes a peripheral face connecting the two faces. This side face 3 includes a curved first portion 4 that extends at the height of the outer face 2 from a portion perpendicular to the faces P1 and P2 towards the inner face 1. The curved first portion 4 extends entirely between planes P2' and P3' parallel to planes P1 and P2 and has a thickness f measured perpendicular to planes P2' and P3', the thickness f being strictly less than the total thickness e. Alternatively, one may envisage a substrate having a planar inner surface 1 and geometrical datum equivalent to that of FIG. 1d.

[0028] Figure 1e shows an initial substrate 10 according to variant 5, in which the two faces, the outer face 2 and the inner face 1, are planar and parallel. The side face 3 includes a first portion corresponding to the bevel 4, as in variant 2, and also includes a second portion including a groove. This side face further includes several rounded corners.

[0029] In any case, the total thickness e of the initial substrate 10 and thus of the small watch glass is between 0.2 mm and 15 mm, or between 0.85 mm and 15 mm, or between 1.45 mm and 11 mm. Moreover, regardless of the glass geometry, a visual effect corresponding to a color modulation can be achieved by the angle α of the side surface 3 being equal to or greater than 10°, preferably equal to or greater than 15° or equal to or greater than 30°. Moreover, regardless of the glass geometry, a particular portion 4 of the side surface 3 can have a variable area compared to the area of ​​the inner surface 1, which may be between 1% and 30%, or between 1% and 18%, or preferably between 10% and 18%.

[0030] Once the substrate has been provided as a result of this previous step, the manufacturing method performs two main steps, which constitute the initial substrate coloring stage.

[0031] The first step consists of introducing E1 at least one colouring chemical element.

[0032] According to a first implemented variant, this introduction step is carried out by depositing, on at least one of the two faces, either internal or external, of the initial substrate, a coating containing at least one coloring chemical element, for which purpose this coating can be deposited by one of the following methods: -Physical vapor deposition (PVD), in particular magnetron sputtering (MS); or -Physical vapor deposition (PVD), especially thermal evaporation; or - Chemical vapor deposition (CVD); or -Atomic Layer Deposition (ALD); or -Spin-on, dip-coating or sol-gel type liquid layer deposition.

[0033] According to the second implemented variant, this introduction step is carried out by recoil ion implantation, in particular when the diffusion of the coloring chemical element introduced in the form of a coating on the substrate is slow or requires too high temperatures. The term "recoil ion implantation" refers to the combination of depositing at least one coloring chemical element in a thin film coating by PVD, CVD and / or ALD and bombarding said coating with a gas such as argon and / or nitrogen and / or oxygen.

[0034] According to these variants of introducing at least one coloring chemical element, a coating is applied to at least one surface of the initial substrate, in particular to at least one of the outer or inner surfaces. This coating may be homogeneous or consist of superimposed layers of different elements. FIG. 2a shows the result obtained after introducing a coating 20 to the inner surface 1 of the substrate. This step allows a very precise deposition of the thickness e' of the coating. The coating thickness e' may be between 1 nm and 10 μm, in particular between 1 nm and 1 μm. This thickness e' may define the color to be obtained in the future and the transparency of the resulting colored transparent piece, in particular a small watch glass. This allows a middle ground to be struck. If the coating thickness is too small, the coloring cannot be carried out; this defines a lower limit for the thickness e'. If the coating thickness is too large, sufficient transparency of the substrate cannot be maintained; this defines an upper limit for the thickness e'. This thickness range depends on the coloring chemical element, the transparent material of the substrate and the applied heat treatment, as will be explained in more detail below.

[0035] Furthermore, the coating may be uniform, in other words, have a constant thickness across the surface of the substrate to achieve a homogeneous result. Alternatively, it may be desirable to obtain a mixed result; in this case, the coating need not be uniform.

[0036] For example, the coating may be discontinuous. The method therefore includes a previous step consisting of depositing a mask, for example of resin, on the coating application surface in order to obtain a partial coating outside the masked zone. The mask is then removed after the coating has been applied. The masking may be more or less dense so as to form a color gradient as a function of the masking density.

[0037] Alternatively, a coating can be applied to the surface of the substrate without regard to the features, and then the features can be revealed by selectively removing layers.

[0038] For example, a coating having a variable thickness can be deposited by a directional vacuum method such as MSPVD deposition. A thickness gradient of the coating 20 can be achieved by tilting the substrate during deposition, by appropriate masking, or by other suitable techniques.

[0039] Alternatively, the introduction of at least one coloring chemical element can be performed by direct ion implantation, without the need for a coating. The disadvantage of this latter alternative lies in the difficulty of controlling the amount of coloring chemical element introduced into the substrate, and in the difficulty of obtaining high definition of the features by masking.

[0040] Preferentially, the introduction of at least one colouring chemical element is carried out on one of the inner or outer faces of the substrate, as a variant, on two faces, the inner and the outer face, or also on some or all of the faces 3.

[0041] The coloring chemical elements can be selected from the following non-exhaustive list: - a metallic element, in particular chosen from the transition metals; or - oxides, especially metal oxides, especially made from transition metals; or - Metal alloys; or - Metalloids, nonmetals or gases.

[0042] The coloring chemical elements are combined with the substrate material to obtain the desired color. In particular, it is known to use cobalt to color an alumina substrate blue. Of course, other colors can be obtained by using coloring elements such as iron, titanium, gold, chromium, vanadium, copper, manganese, magnesium, zinc, silver, boron, nitrogen, etc., alone or in combination. Thus, several different elements, for example several coloring chemical elements from the above list, can be combined. For example, red can be obtained by adding chromium or gold to alumina, and blue can be obtained by adding titanium and iron in combination.

[0043] The method advantageously includes a step of cleaning the substrate prior to the step of introducing the coloring chemical elements, the cleaning consisting of a detergent wash followed by rinsing and drying operations.

[0044] The method then comprises carrying out a second main step E2 of thermal treatment of the substrate resulting from the introduction step E1, comprising at least one colouring chemical element, said thermal treatment comprising carrying out a step of heating the substrate resulting from the preceding step, maintaining the substrate at a holding temperature for a holding period and then a step of cooling the substrate.

[0045] The maximum holding temperature is particularly important to perform the function of transferring the coloring chemical elements into the initial substrate. The holding period can influence the amount of diffused and / or reacted coloring chemical elements and thus adjust the color intensity of the final color. It can therefore be chosen within a very wide range. Finally, the temperature ramp rate is secondary to the coloring function and is chosen to avoid attacking the initial substrate, in particular to avoid heat shock.

[0046] Advantageously, the holding temperature is between 500° C. and 1850° C., or between 800° C. and 1400° C., and in particular in the case of an initial substrate made of monocrystalline alumina with a cobalt coating as the result of the introduction step E1, between 900° C. and 1200° C. The associated holding period can be very long (up to several days). In the case of an initial substrate made of monocrystalline alumina with a cobalt coating as the result of the introduction step E1, the period is advantageously between 0.5 and 48 hours, more generally between 0.5 hours and 4 days.

[0047] The heat treatment can be carried out under air. According to one variant, the heat treatment is carried out in a controlled inert, oxidizing or reducing atmosphere or under vacuum. In particular, the heat treatment can be carried out under a nitrogen atmosphere. According to a further variant, the gas flows and pressures can be different. Furthermore, the second heat treatment step E2 can be carried out in a second part of an apparatus different from the first part of an apparatus provided for carrying out the first introduction step E1. Alternatively, this second step E2 can be carried out in the same piece of equipment used for the first introduction step E1.

[0048] FIG. 2b illustrates the result obtained by heat treatment of the substrate resulting from the first step shown in FIG. 2a. As a result of the heat treatment, a zone 30 of modified chemical composition is obtained near the inner surface 1 and within a thickness d of the volume of the substrate. The modified composition in this zone performs a coloring function. For example, a crystalline alumina with an Al2O3 composition that is initially colorless and transparent can be made blue by adding a measured amount of cobalt to form a modified zone with a CoAl2O4 composition and / or can be made green with a measured amount of cobalt by replacing the cobalt in the alumina to form a modified composition zone. As another example, magnesium can be added to alumina Al2O3 to obtain magnesium aluminate MgAl2O4. According to yet another example, coloring due to the plasmonic effect can be obtained by adding gold to alumina Al2O3. Coloring due to the formation of intermetallic compounds can also be envisaged. This step concludes the process of converting the initial substrate into a transparent and colored piece. The zones 30 of modified chemical composition are thus coloured and, surprisingly, produce the same visual effect as glass which is coloured in the bulk, i.e. throughout its volume and thickness. However, if the colouring is carried out only on one of the inner or outer surfaces, the zones of modified chemical composition are very small and only extend over a thickness d between 30 and 500 nm, which corresponds to an average of less than 25%, or less than 2%, or less than 0.2% and preferentially less than 0.07% of the total thickness e of the watch component. The transparent coloured pieces thus formed always consist mainly of transparent material originating from the initial substrate 10 and a very small volume of transparent material which has been chemically altered and coloured.

[0049] Thus, the method carried out results in transparent colored pieces, without the need for reworking the surface finish or reworking the treated surface. In fact, the thickness e' of the coating of coloring chemical elements may be defined such that the coloring chemical elements completely diffuse into and / or react with the substrate 10 during the thermal treatment. It may possibly not be necessary to remove the coloring chemical element residues by carrying out a process during the thermal treatment in which the total amount of the coloring chemical elements is consumed. Alternatively, the coloring chemical element residues, if any, can be removed by means well known to the person skilled in the art (stripping, dissolving, chemical attack, grinding, etc.).

[0050] The method can include, at the end of the second step, a step of completing the watch component, in particular the small watch glass. For example, if the initial substrate is not a completed small watch glass, for example if it does not have the desired shape, the small watch glass can be obtained by machining the obtained transparent and colored piece, in particular by machining the side of the glass. As an example, a wide sapphire sheet can be made, colored, and then machined, for example with a laser, to obtain smaller watch components, for example nails, wheels, glasses, etc. Preferably, the completion step does not change the bands of modified chemical composition in this component.

[0051] Alternatively, additional machining steps may be carried out simply to form the bevelled surface or peripheral portion 4, in particular the bevelled portion and / or groove or monocular or magnifying lens as illustrated in Figures 1b to 1e, to complete the watch component, in particular the small watch glass.

[0052] As a variant, this step may consist in structuring features in the colored transparent piece, for example by means of a laser, for purely decorative or engraving purposes. Advantageously, therefore, the implementation of laser etching on the small watch glass does not require any adaptation of parameters, regardless of the coloration of the glass obtained according to the invention, since it acts outside the colorless zone of the glass, i.e. outside the area of ​​the modified chemical structure.

[0053] Alternatively, this step may consist in structuring the colored piece. By "structuring" it is meant forming raised and / or recessed zones on at least one outer or inner surface of the colored piece in order to form one or more colored features or features with a color gradient or with the color of the initial substrate by providing a pronounced relief or by modifying the thickness of the coloring. The structuring may be non-through openings, either on the surface or within the thickness of the colored piece. Such openings may be micro- or nano-level openings, preferably of a size sufficiently small to be invisible or practically invisible to the naked eye. Alternatively, such openings may be of a larger, naked eye-visible size in order to be intentionally made visible. In any case, the openings are not limited to being circular, but may have any cross-sectional shape. This cross-section may be, for example, rectangular or star-shaped or have any other suitable shape. Such structuring may in particular be obtained by various conventional machining techniques, or by laser machining, in particular femtosecond laser machining, or by deep reactive ion etching (DRIE) or chemical erosion. The structuring step can be carried out directly on the initial substrate provided at an early stage of the method according to the invention, before carrying out the two main steps of the method. As a variant, the structuring step can be carried out directly on the coating deposited on the substrate, after the first introduction step E1 of the method and before carrying out the second heat treatment step E2 of the method according to the invention.

[0054] An additional step may also consist of assembling the obtained transparent colored piece with other parts, which may or may not be obtained in the same way as the present method. For example, this additional step may consist of assembling the glass with an eyepiece or a magnifying lens, or of gluing, in particular adhesively, the glass to a base having an edge that assembles it to the watch case, or of assembling several glasses.

[0055] Finally, the manufacturing method according to the invention has the following advantages: - the introduction of coloring chemical elements is perfectly controlled in terms of quantity and position, making it possible to adjust and repeat them in each run to obtain the desired and identical result; Likewise, the heat treatment can be controlled and repeated, obtaining the same desired and identical colored transparent pieces each time it is performed; The method is therefore adaptable to mass production and watch requirements.

[0056] The method is equally applicable to the manufacture of any transparent clock component, having a substantially planar or curved internal surface, and consisting mainly of a transparent material colored by a zone of modified chemical composition in the component by introducing at least one coloring chemical element, said zone of modified chemical composition extending only over a portion of the total thickness of the clock component, i.e. not over the entire thickness of the component, said portion corresponding to an average of not more than 25%, or not more than 2%, or not more than 0.2% of the total thickness of the clock component, measured in a direction perpendicular to the internal surface of the component or perpendicular to a tangent formed at the apex of the internal surface of the component. Advantageously, the zone of modified chemical composition extends on average over a thickness corresponding to at least 0.0002% of the total thickness of the clock component. Said thickness of the clock component is advantageously substantially the thickness of the initial substrate. As a variant carried out, said thickness of the clock component may be reduced with respect to the initial total thickness of the initial substrate, but keeping the thickness of the zone of modified chemical composition in the above range.

[0057] Thus, for example, the invention applies to the manufacture of small watch crystals, monoculars, magnifying lenses, parts of back metals, dials, date dials, decorations for watch movements, lugs, cars.

[0058] According to the method of the invention, the watch component obtained has the following advantages: - the colouring is predictable (especially in terms of the shade of blue and in terms of saturation), repeatable and arranged in the desired way: the colouring may be homogeneous over the entire intended surface, which may be very large, as in the case of sapphire glass, or it may be a controlled mixture of colourings, with controlled gradients, defined features or inscriptions. It gives the impression of colouring throughout, despite the thinness of the bands of chemical structures modified to be coloured. It also gives a visual impression independent of the internal or external surfaces that have been treated and independent of the total thickness of the watch component; - transparency ensures, for example in the case of small watch glasses, the readability of the time or time-derived indications, the visibility of the dial and of the flange of the case body, and in addition, it also makes it possible to selectively charge (excite) and emit (emit) luminescent materials, in particular photoluminescent (phosphorescent and / or fluorescent) materials, present underneath the glass (in or on the chapters, hands, transfers, etc.); - the mechanical strength of the entire initial substrate is maintained as a result of the manufacturing method: the manufacturing method does not cause any deterioration of mechanical properties; the surface hardness of the initial substrate is maintained in the colored transparent piece resulting from this manufacturing method; - the appearance of the watch component is free from defects such as isolated uncolored, miscolored or "over-colored" zones, pitting, localized opaque appearance, through-holes, halos, etc. The entire surface of the resulting colored transparent piece, which may be large in size and is fully visible by the user, optionally even backlit, is free from the above-mentioned defects; - this effect can be adjusted by means of inclined additional surfaces at the height of the lateral surfaces of the timepiece component, for example having a bevelled shape; The above-mentioned effects, for example of forming raised and / or recessed structural zones on at least one surface of the timepiece component and / or of forming structural zones within the thickness of the timepiece component, can be adjusted by other geometrical considerations.

[0059] The invention will now be illustrated by means of several successive examples.

[0060] According to a first series of embodiments, a colorless, transparent, single crystal alumina substrate 10 has a shape that corresponds to the final shape of a finished watch glass suitable for installation in a watch. This transparent implementation corresponds to the "reference" implementation in the tables and various examples below.

[0061] According to this example, the reference small watch glass has a diameter of 29.5 mm and a total thickness of 1.8 mm. This glass has a shape similar to that illustrated in FIG. 1e, with a chamfer around the outer surface for a height f of 0.8 mm, inclined at 36°, and grooves or other machined features on the remaining height of the side 3. Its outer and inner surfaces are polished.

[0062] The initial substrate, corresponding to the reference watch glass described above, is washed in a cleaning bath with detergent, then rinsed and dried, and placed in the chamber of a thermal evaporation PVD device. A cobalt metal coating is then deposited on the internal surface of the initial substrate, corresponding to the first main step of the method described above. The deposition rate and time are adjusted so that the coating has a predetermined thickness. The deposition thickness is verified by X-ray refractive index measurement. This operation is repeated to form a series of colored strips with several different coating thicknesses e' (set value) in the range of 5 nm to 80 nm, as summarized in the table below. The heat treatment according to the second main step of the method is carried out by holding at 1060° C. for 2 hours, the same for all strips from the series.

[0063] Spectral photometric colorimetry measurements are carried out in transmission through colored pieces formed as some samples 1.1 to 1.9 resulting from the thermal treatment step as a result of the method according to the present invention. The table below shows the results in the CIE LaB space. The transmission measurements are carried out between 360 nm and 740 nm with the CIE standard illuminant D65 and an observer at 2°. The luminous intensity L*, the color values ​​a* and b*, the chroma C* and the hue h* (or hue angle) are measured. The transmission values ​​(T%) are recorded at 360 nm and 460 nm. Y is the transmission; it takes into account the sensitivity of the eye and the type of illumination: it is calculated by integrating the transmission spectrum weighted to the response function of the human eye (centered in the green part of the visible spectrum) and the spectrum of the CIE standard illuminant D65 as defined in the "Technical Report of Colorimetry" CIE15:2004. These results show, in particular, that the difference in coating thickness e' has a direct effect on the resulting blue color saturation and hue in a manner perceptible to the naked eye. The glasses resulting from the introduction step E1 have a more opaque and increasingly metallic gray appearance with each increasing thickness e'. The glasses resulting from the heat treatment step E2 have an increasingly saturated blue appearance while maintaining transparency in the cobalt thickness range e' between 5 nm and 45 nm. Above this thickness, the applied heat treatment reduces transparency and therefore transmission.

[0064] For example, in sample 1.9 (e'=80 nm), the transmittance is equal to: - 55.0% at 460 nm, so readability through this glass is no longer sufficient. At -360 nm it is 38.0%, and the charge of the photoluminescent (phosphorescent and / or fluorescent) material through the glass is no longer sufficient.

[0065] In the specific case of this series of examples, samples with a thickness e' of 12 nm or less allow excellent readability. Samples with a thickness e' of 45 nm or less allow acceptable readability. At a thickness e' of 80 nm, the sample can only provide dim readability, since the glass is semi-transparent. At a thickness e' of 80 nm, the glass becomes more opaque, so readability becomes more difficult.

[0066] The table below shows the results obtained for the series of samples in the first example: [Table 1]

[0067] To illustrate these results, Figure 3a shows the spectra of transmittance (T%) as a function of wavelength (Lnm) for several coating thicknesses in the series of Example 1. Figure 3b is an enlarged view of Figure 3a.

[0068] In addition, when looking at the glass, the tint appears darker through the peripheral bevel than through the flat outer surface. In other words, the tinting effect is modulated by the angle α. The reason for this is the shape of the tinted pieces. As mentioned above and illustrated in figures 1b to 1e, it is possible to show the advantages of providing a bevelled portion at the height of the outer surface of the glass.

[0069] The observed blue hue results from cobalt aluminate, potentially CoAl2O4, which arises during the heat treatment from a chemical reaction of cobalt, alumina and oxygen at the height of the zone of modified chemical composition of the resulting colored transparent piece. Figure 3c is an image obtained by a transmission electron microscope (TEM) of a thin section obtained by focused ion beam (FIB) from the resulting colored transparent piece, perpendicular to its internal surface. The insert in the figure shows an electron diffraction image obtained from a zone close to the treated internal surface, more precisely at a distance d or less from the surface. This image allows the formation of cobalt aluminate and thickness d during the coloring stage of the sapphire glass.

[0070] The overall mechanical properties of the glass obtained are not diminished by the implementation of the method according to the invention. This result is verified from batches of additional samples of small watch glasses, always obtained from the same reference substrate, coated with cobalt layers of various thicknesses by magnetron sputtering, and then heat-treated by holding at 1000° C. for 3 hours. The breaking strength and hardness of the glass are not in any way affected by the presence of the colored and modified zones of chemical composition.

[0071] According to series 2 of Example, the colorless transparent monocrystalline alumina initial substrate 10 used has a shape corresponding to the final shape of the finished watch glass, called "reference", in the same way as in series 1 of Example above. Samples of colored pieces are made by varying the heat treatment carried out, more particularly by varying the holding temperature during the 3 hours. All these samples were pre-coated on the inner surface of the substrate by depositing 10 nm of cobalt metal by thermal evaporation.

[0072] The following table shows the results obtained from these examples: [Table 2]

[0073] Additionally, FIG. 4 constitutes the spectra of the transmittance (T%) as a function of wavelength (L nm) at several holding temperatures (Tp ° C.) according to this series of Example 2.

[0074] In particular, samples 2.1 to 2.3 have a hue angle that increases with the holding temperature, sample 2.1 being green and samples 2.2 and 2.3 being blue. Above 1400°C treatment (sample 2.4), the sapphire glass becomes transparent and colorless, just like the untreated sapphire glass (reference sample).

[0075] According to series 3 of example, samples can be obtained in a similar manner to series 2 of example, but varying the heat treatment hold from 30 minutes to 48 hours, with a hold temperature always equal to 900° C. All samples are previously coated by thermal evaporation to deposit 5 nm of cobalt metal on the inside of the substrate.

[0076] The following table shows the results obtained from these examples: [Table 3]

[0077] In addition, FIG. 5 shows the spectra of transmittance (T%) as a function of wavelength (L nm) at several retention times (th) according to the series of Example 3.

[0078] In particular, the longer the duration of the heat treatment, the more efficiently the coating reacts with the glass, thereby increasing the transmittance and establishing the blue color. After heat treatment with a hold time of 3 hours (Example 3.3), the sapphire glass is blue and has sufficient transparency at wavelengths to allow readability and emission of any charge and photoluminescent material.

[0079] According to series 4 of embodiment, the initial substrate 10 used always corresponds to a finished reference watch glass, in the same way as series 1 of embodiment described above. This series is carried out by varying the applied heat treatment, more particularly the applied temperature and / or duration. All samples are implanted beforehand with iron, cobalt or titanium by the method of ion implantation with ion beam (direct implantation of ions of an ion beam).

[0080] The following table shows the results obtained from these samples: [Table 4]

[0081] In addition, Figures 6a to 6c show the spectra of transmittance (T%) as a function of wavelength (Lnm) for a series of samples according to Example 4.

[0082] In particular, iron (at 900°C and 1000°C) gives an orangey color, cobalt gives a gray color at 900°C and a blue color at 1000°C, and titanium gives a yellowish color (at 900°C and 1000°C). Treatment at 1600°C with either iron or cobalt forms a transparent, colorless glass.

[0083] The values ​​of hardness and elastic modulus of the sapphire glass obtained by nanoindentation of the samples forming this series of Example 4 allow us to conclude that under the test conditions, the mechanical properties (hardness and elasticity) of the sapphire glass are not affected by the coloring method involving ion implantation and heat treatment.

[0084] According to series 5 of the embodiment, the colourless and transparent monocrystalline alumina initial substrate 10 used has a shape which corresponds to the finished shape of a finished reference watch glass, called reference watch glass, in the same manner as in series 1 of the embodiment described above.

[0085] An initial substrate, corresponding to a reference small watch glass, is washed in a cleaning bath with detergent, then rinsed and dried, and placed in the chamber of a thermal evaporation PVD apparatus. A cobalt metal coating is then deposited on the internal 1 or external and inclined surfaces 2+4 of the initial substrate. This operation is repeated to form a series of colored strips with several different coating thicknesses e' (set values) of 3, 6 or 9 nm, as summarized in the table below. The aforementioned implantation is carried out by the plasma immersion method with argon ion bombardment, in the same piece of equipment for all strips in a series of runs; only one implantation ion dose varies (D is atoms / cm at an energy of 10 kV, as summarized in the table below). 2 These steps correspond to the first main step of the method described above.

[0086] The heat treatment according to the second main step of the above method is carried out identically for all pieces in the series, by holding at 1000° C. for 3 hours.

[0087] The following table shows the results obtained from these samples: [Table 5]

[0088] In addition, FIG. 7 shows the spectra of transmittance (T%) as a function of wavelength (L nm) for several coating thicknesses e′ and implanted ion doses D according to this series of Example 5.

[0089] In particular, the samples obtained are blue; samples 5.1 to 5.3 and 5.4 to 5.6 have a chroma C* that increases with coating thickness e'. With identical processing parameters, the results are similar regardless of the surface treated (surface 1 or surfaces 2+4).

[0090] This Example 6 focuses specifically on the effect on the charge (excitation) and emission (light emission) performance qualities of a photoluminescent material located on the dial under the inner surface of a colored watch glass, in this example blue. A blue glass (Sample 6) is prepared according to the embodiment, in which a colorless and transparent single crystal alumina substrate 10 is subjected to a 9 nm cobalt deposition by thermal evaporation, followed by a heat treatment at 1060° C. for 2 hours.

[0091] The results of the spectral photometric colorimetry measurements in transmission carried out on Sample 6 and the reference glass are shown in the table below. [Table 6]

[0092] For the same watch, containing markings and hands with commercially available photoluminescent material, two glasses (reference glass and glass sample 6) are presented in succession. After placing the watch in the dark for more than 24 hours, the luminous performance quality of the watch combined with the blue glass (sample 6) and the watch combined with the reference glass, subjected to standard illumination (CIE standard illuminant D65 at 400 lux for 20 minutes), is compared. The luminous degradation [nDd] as a function of the time placed in the dark is measured photometrically. The relative decrease in the luminous performance quality of the blue glass (sample 6) is evaluated as a percentage of the luminous intensity of the reference glass.

[0093] The relative decrease in luminosity performance quality due to coloration for sample 6 is 0.8% from 0 to 8 hours and 1.7% from 0 to 22 hours.

[0094] The use of the blue glass according to Example 6, compared to the colorless reference glass, has no effect visible to the watch wearer on the performance quality of the tested photoluminescent material.

[0095] Naturally, the above examples are provided in a non-limiting manner to illustrate the results that can be obtained by implementing the concepts of the present invention, which may be applied with equal effect to any transparent watch component other than a miniature watch glass.

[0096] The results described clearly show the advantages obtained by using the method of the invention. On the basis of this description, the skilled person will know how to adjust the deposition thickness e', the materials used and the parameters of the heat treatment as a function to achieve the desired result, in particular with regard to color and transparency. In particular, it will be advantageous to select to achieve a transmittance (Y) of 68% or more, or 79% or more. The substrate may be selected in particular for small watch glasses such that the watch component obtained has an average hardness of the outer surface of 30 GPa or more and / or 2016HV0.2 or more. [Explanation of symbols]

[0097] 1. Inside 2 External surface 3. Aspects 4 Sloped section 10 Initial board 20 Coating

Claims

1. A transparent timepiece component comprising a substrate entirely made of a transparent material, said transparent material being coloured by a zone of modified chemical composition in said component by introducing at least one colouring chemical element into said transparent material, said zone of modified chemical composition extending through only one side of the total thickness of said substrate of said timepiece component, The substrate has a total thickness of 0.2 mm or more and 15 mm or less, A transparent watch component, wherein the thickness of the modified chemical composition zone is between 3 nm and 45 nm, and the transmittance of the colored transparent material is 68% or more.

2. A watch component as described in claim 1, wherein the colorless or pre-colored transparent material is an inorganic and / or mineral material, or the transparent material consists at least in part of an inorganic and / or mineral substance.

3. A watch component as described in claim 1 or 2, wherein at least one colouring chemical element is selected from metals, and / or metal oxides, and / or metal compounds and / or metal alloys, and / or transition metals, and / or transition metal oxides and / or metalloids and / or non-metals and / or gases.

4. A watch component as described in claim 3, wherein at least one colouring chemical element is selected from cobalt, and / or iron, and / or chromium, and / or gold, and / or titanium, and / or vanadium, and / or copper, and / or manganese, and / or magnesium, and / or zinc, and / or silver, and / or boron, and / or nitrogen.

5. 5. A timepiece component according to any one of claims 1 to 4, wherein the zone of modified chemical composition contains cobalt aluminate and / or cobalt to obtain a blue and / or green timepiece component, or wherein the zone of modified chemical composition contains gold to obtain a pink or red timepiece component.

6. A watch component as claimed in any one of claims 1 to 5, wherein the substrate has an area of ​​20 mm 2 or more.

7. A watch component as claimed in any one of claims 1 to 6, wherein the substrate is a small watch glass having an area of ​​80 mm 2 or more, or 200 mm 2 or more, or 300 mm 2 or more.

8. A watch as claimed in claim 6 or 7, which is transparent so that the display can be read through its thickness. Component parts.

9. A watch component as described in claim 8, wherein the substrate, a watch glass, includes an outer surface and an outer side inclined relative to the outer surface, the inclination being at least 10°, or at least 15°, or at least 30° relative to a direction perpendicular to the inner surface of the watch glass in order to adjust the coloring effect of the watch glass, and / or including a structural band raised and / or recessed on at least one surface of the watch component and / or a structural band within the thickness of the watch component.

10. A watch component as described in claim 9, wherein the inclined outer surface constitutes between 1% and 30% of the range of the inner surface, or between 1 and 18% of the range of the inner surface, or between 10 and 18% of the range of the inner surface.

11. a. A gradient in the thickness of the zone of modified chemical composition to adjust the coloring effect of the watch component; and / or b. discontinuities in said zones of altered chemical composition 11. A timepiece component according to any one of claims 1 to 10, comprising all or some of the features of

12. A watch comprising a watch component according to any one of claims 1 to 11.

13. A method for manufacturing a timepiece component according to any one of claims 1 to 11, comprising the steps of: a. providing an initial substrate (E0) including a substantially planar or curved inner surface made primarily of a transparent material; b. An introduction step (E1) of introducing at least one coloring chemical element through at least one outer or inner surface of said initial substrate; c. a heat treatment step (E2) of heat treating the substrate resulting from the introduction step (E1) containing at least one coloring chemical element in order to obtain a transparent colored piece; 2. A method for producing a colored transparent watch component, comprising:

14. A method for producing a watch component as described in claim 13, wherein the introducing step (E1) comprises a step of depositing a coating of at least one colouring chemical element on at least one surface of the initial substrate, and / or the introducing step (E1) comprises a step of recoil ion implanting at least one colouring chemical element.

15. A method for manufacturing a watch component as described in claim 14, wherein the watch component is a small watch glass and the introducing step (E1) includes a step of depositing a coating having a thickness of 1 nm to 10 μm, or 1 nm to 1 μm.

16. A method for producing a watch component as described in any one of claims 13 to 15, wherein the introduction step (E1) includes a step of depositing a coating and a preliminary step consisting of masking the surface of the substrate so as to avoid receiving the coating and / or to form a coating of variable thickness.

17. A method for manufacturing a watch component as described in any one of claims 13 to 16, wherein the heat treatment step (E2) includes holding at a holding temperature between 500°C and 1850°C, or between 800°C and 1400°C, or between 900°C and 1200°C, for a holding period of between 0.5 and 48 hours, or between 0.5 hours and 4 days.

18. a. machining a transparent colored piece to form said watch component; and / or b) machining at least one surface of the transparent colored piece to modify its shape and / or to form features and / or to form an inclined outer surface with respect to the outer surface of the timepiece component, with respect to a direction perpendicular to the curved surface, of 10° or more, or 15° or more, or 30° or more; and / or c. combining the transparent colored piece with other watch components; and / or d. Removing residual coloring chemical elements from the surface of the transparent colored piece; and / or e. Etching a feature into said timepiece component.

18. A method for manufacturing a timepiece component according to any one of claims 13 to 17, comprising all or part of the additional steps of:

Citation Information

Patent Citations

  • Glass having low transmissivity

    JP1991257042A

  • Cover glass for wristwatch and its production

    JP1997048626A

  • Coloring method for glass

    JP2004352561A

  • Ornament, clock, electronic equipment and manufacturing method of ornament

    JP2006248044A

  • Timepiece, light-transmitting member, and its manufacturing method

    JP2009186226A